The impact of facebook content towards student behaviour in UiTM Campus Rembau / Nur Azimah Ahmad Bahtir - Ahmad Bahtir, Nur Azimah (2018)
Facebook is one of the social media that have been use by people around the world as one of the easy way of communication. There are many students still use this social media. Facebook content allows them to do many things. However, the Facebook content give a lot of beneficial and also damaging to student that could impact on their behaviour. The goal of this study is to determine the impact of Facebook content towards student behavior. In order to gain the result, I had distributed the questionnaires to 30 respondents in UiTM Campus Rembau and then did the analysis upon the data collected. I hope this research motivate others to do further research on the same subject that involving student behaviour.